Effectiveness of Premarital Sex Education on Sexual Dysfunctional Beliefs of Couples, Isfahan - ameneh Dashtestannejad; ronak Eshghi; emaneh Afkhami (Zanjan University of Medical Sciences and Health Services, 2015)
Background and Objectives: Given the importance of sexual relationships in marriage and influence of beliefs on types of sexual activities, it seems that premarital sex education can prevent some marital problems and increase sexual knowledge. The aim of this study was to determine the effectiveness of premarital sex education on improvement of coupleschr('39') sexual dysfunctional beliefs in Isfahan. Materials and Methods: This was a quasi-experimental pretest-posttest study with a control group. Participants were selected from married couples referring to Imam Ali Charity Center in Isfahan in 2013. Participants were randomly assigned to the experimental (15 pairs) and control groups (15 pairs). Data were gathered using the male and female versions of the Nober and Pintogoviachr('39')s Sexual Dysfunctional Beliefs Questionnaire. The experimental group received eight sessions of premarital sex education. The control group was in waiting list. Results: The results of the ANCOVA analysis showed that the educational intervention was effective in sexual dysfunctional beliefs among women (p<001) and men (p<001). Conclusion: Premarital sexual skills training can improve sexual dysfunctional beliefs in men and women. Sex education, especially before marriage, can prevent sexual disorders and increase coupleschr('39') sexual satisfaction and marital intimacy.